Reproductive health knowledge and attitudes toward adolescent mental health - Fiorensa Aprilianfa Rattu; Hilman Adam; Irny Maino (JOURNAL OF Mental Health Concerns, 2026)
Background: Reproductive health is a state of complete physical, mental, and social well-being related to the reproductive system, its functions, and processes, not merely the absence of disease or disability. Lack of knowledge about reproductive health among adolescents can lead to various problems such as unintended pregnancy, abortion, early marriage, sexually transmitted infections (STIs), and HIV/AIDS. Therefore, adequate knowledge and positive attitudes toward reproductive health are essential to prevent these risks, especially among high school students. Purpose: To describe the level of knowledge and attitudes toward reproductive health among adolescents. Method: A quantitative design with an analytic survey approach. The sampling technique used was non-probability sampling with a purposive sampling method. The population consisted of 282 students, with a sample of 247 respondents. Data were collected using a questionnaire and analyzed using Microsoft Excel and the Statistical Programmer for Social Science (SPSS). Results: The majority of respondents had good knowledge, with 214 students (86.6%) categorized as having a high level of knowledge. In terms of attitude, most respondents also demonstrated positive attitudes toward reproductive health, with 162 students (65.6%). Conclusion: Most adolescents have good knowledge and positive attitudes regarding reproductive health. However, continuous education is still needed to maintain and further improve awareness and positive attitudes toward reproductive health.   Keywords: Attitude; Adolescents; High School Students; Knowledge; Reproductive Health.